Non-Structural Mitigation Through Media Literacy on Cyclone Disaster in West Muna Regency - Ruslanjari, Dina; Dewi, Titis Puspita; Puspitasari, Anisa Eka (KnE Social Sciences, 2019)
Cyclone disaster is the second most deadly disaster in Indonesia after flooding. Cyclones mostly occur during the transitional period from dry season to rainy season. West Muna Regency is one of the regions which started to experience cyclones as a disaster in 2015 where they experienced the most immense disaster that has occurred on record. This disaster caused 600 houses in three districts namely North Tiworo District, South Tiworo District, and Tiworo Archipelago District to be heavily damaged. The magnitude of the disaster was caused by the distribution of area in the three districts which are generally comprised of floating villages far from Muna Island mainland. Cyclone disasters which occur in West Muna Regency requires attention in which one form is non-structural mitigation. Non-structural mitigation can be embodied in the forms of law formulation, formulation of a hazard map, formulation of a risk map, zonation, education, counseling, and emerging awareness toward the community. The focus of this research was recommending the implementation of non-structural mitigation through media literacy, which is categorized as establishing awareness within the community. This research as aimed to enhance the awareness and knowledge of the community related to cyclone disaster. The research method used was a qualitative descriptive by performing depth interviews with community figures. The results of this research have indicated that media literacy is a method of non-structural mitigation which is effective and in accordance with the development of the era. The implemented media are printed or social media because both media are considered relevant as the socialization media regarding the knowledge of cyclones. Keywords: cyclone, media literacy, non-structural mitigation